(untitled) (World Bulletin of Public Health, 2026)
This study provides an extensive scientific examination of the physical development of young athletes, focusing particularly on the functional condition of the respiratory and cardiovascular systems and the physiological effects of consistent sports training on these systems. Current research indicates that regular physical activity accelerates morphofunctional growth, improves cardiorespiratory performance, and supports adaptive physiological responses in the developing body. The results highlight the essential role of structured training in enhancing somatic growth, functional potential, and overall health outcomes among youth participating in sports